Efficacy of Resveratrol in Experimental Subarachnoid Hemorrhage Animal Models: A Stratified Meta-Analysis - Tan, Jiahe; Song, Rui; Luo, Siyue; Fu, Wenqiao; Ma, Yinrui; Zheng, Lian; He, Zhaohui (Frontiers in Pharmacology, 2022)
Background: Subarachnoid hemorrhage (SAH) is a serious neurosurgical emergency with extremely high morbidity and mortality. Resveratrol (RES), a natural polyphenolic phytoalexin, is broadly presented in a wide variety of plants. Previous research had reasonably revealed its neuroprotective effects on experimental SAH animal models to some extent. But the results were more controversial. Therefore, we conducted a meta-analysis to evaluate the evidence on the effectiveness of RES in improving outcomes after SAH animals. Methods: A systematic literature review was conducted in the PubMed, EMBASE, and Web of science databases to incorporate experimental control studies of the efficacy of RES on SAH models into our research. The standardized mean difference (SMD) was used to compare the brain water content (BWC) and neurological score (NS) between the treatment and control group. Results: Overall, 16 articles published from 2013 to 2022 met the inclusion criteria. The meta-analysis of BWC showed a significant difference in favor of RES treatment (SMD -1.026; 95% CI -1.380, -0.672; p = 0.000) with a significant heterogeneity (Q = 84.97; I2 = 60.0%; p = 0.000). Further stratified analysis were performed from methodological differences, especially dosage, time of treatments, and time point of outcome assessment. The meta-analysis of NS showed a significant difference in favor of RES treatment (SMD 1.342; 95% CI 1.089, 1.595; p = 0.000) with a low heterogeneity (Q = 25.28; I2 = 17.9%; p = 0.223). Conclusions: Generally, RES treatment had an improvement in both pathological and behavioral outcomes in SAH animal models. The results of this study may provide a reference for preclinical and clinical studies in the future to some extent with great significance for human health.